THE THE HABITS OF THE BUGIS COMMUNITY IN IMPROVING THE MORAL EDUCATION OF ELEMENTARY SCHOOL STUDENTS IN SIDRAP REGENCY - Muchsin Muchsin; Mahsyar Mahsyar; Marhani Marhani; Ahdar Ahdar; Abdul Halik (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2026)
This research aims to comprehensively analyze the Bugis community's practices in encouraging the moral education of elementary school students in Sidrap Regency. The research uses a descriptive qualitative approach by using data collection techniques including participatory observation, in-depth interviews, and documentation that involves teachers, parents, religious leaders, traditional leaders, and students. Data analysis is conducted through stages of reduction, data presentation, and continuous conclusion drawing. The research results indicate that the habituation of students' morals is manifested through several cultural practices, including respect for parents and teachers (mappesona), etiquette for visiting and meeting others (mappatabe), and dining etiquette. The habituation process is reinforced by the exemplary behaviour of parents and community leaders; cultural and religious homogeneity; the alignment of cultural values with Islamic teachings; and the support of school religious-social programmes. However, the main challenge arises from the modernisation of digital technology and the exploratory nature of elementary school children's development. This research emphasises that habits based on Bugis local culture have strategic significance as an effective, integrative, and relevant model of moral education to shape students' characters in facing the dynamics of the global era.